Group-Size Effect on Vigilance and Foraging in a Predator-Free Population of Feral Goats (Capra hircus) on the Isle of Rum, NW Scotland - Shi, J; Beauchamp, G; Dunbar, R (2010)
Many previous studies have found that as group size increases, individual vigilance levels decrease and forage intake increases (group-size effect), but few such studies have considered the impact of within-group interactions and other confounding factors on the direction of group-size effects. A free-ranging population of feral goats (Capra hircus), with little predation threat, was studied on the Isle of Rum (northwest Scotland), from Jun. to Nov. 2000, to investigate the effects of group size on individual vigilance levels and foraging efficiency after taking into account the effect of confounding factors (e.g. sex, season, time of day, habitat, predation risk) and within-group interactions (via changes in movement rates while feeding). Our results show that, while group size exerted a negative influence on individual vigilance levels and a positive effect on movement rate, foraging efficiency never increased with group size and even decreased at certain times of day. There was no sex difference in individual vigilance in feral goats, but foraging efficiency was higher in females than in males. Goats were more vigilant in fall than in summer. The results imply that the benefits for foraging obtained from the reduced vigilance level in larger groups may be constrained or offset by increased interaction (or competition) within larger groups even in a population that faces negligible predation risk. © 2010 Blackwell Verlag GmbH.